Evaluation of Fish Sausage Product using Striped Snakehead (Channa striata) Species at UNICA Enterprise, Phnom Penh - Touch, Sopheap; Chhe, Chinda; Serey, Mardy; Srun, Marnick (Journal of Educational Technology and Learning Creativity, 2025)
Purpose of the study: This study developed and evaluated a novel fish sausage utilizing the Striped Snakehead (Channa striata), an abundant yet underutilized species in Cambodia, to address the limited valorization of local fishery resources and the inconsistent quality of existing products. Methodology: Three formulations with varying concentrations of sugar, salt, and corn starch were systematically assessed through physicochemical, microbiological, and sensory analyses. Physicochemical parameters included pH, water activity, and nutritional composition (protein, fat, and caloric value). Microbiological safety was verified by testing for E. coli, Salmonella spp., and total aerobic counts, while sensory attributes were evaluated by 30 panelists using a 9-point hedonic scale. Main Findings: Results identified Treatment 3 as the optimal formulation, achieving the highest overall sensory acceptance (7.46) and significantly superior taste scores (p < 0.001). All formulations met international food safety standards, with pathogenic bacteria undetected. A central contribution of this research is the development and validation of a specific Hazard Analysis and Critical Control Points (HACCP) plan. Three Critical Control Points (CCPs) were identified: raw material reception, bone removal, and drying. Novelty/Originality of this study: This study addresses the "absence of a HACCP plan" that previously hindered consumer trust. This research provides a clear pathway for the industrialization of safe, high-quality fish sausage, contributing to the economic valorization of Cambodia’s aquatic resources and offering a practical model for local food processors to meet regulatory standards.